2016
DOI: 10.4103/2156-7514.197026
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging Characteristics of the Common Renal Cell Carcinoma Subtypes: An Analysis of 544 Pathologically Proven Tumors

Abstract: Objectives:The objective of this study was to define the characteristic imaging appearances of the common renal cell carcinoma (RCC) subtypes.Materials and Methods:The Institutional Review Board approval was obtained for this HIPAA-compliant retrospective study, and informed consent was waived. 520 patients (336 men, 184 women; age range, 22–88 years) underwent preoperative cross-sectional imaging of 544 RCCs from 2008 to 2013. The imaging appearances of the RCCs and clinical information were reviewed. Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…The results from the QUADAS-2 analysis are presented in Table 2. The risk of bias in patient selection was classified as unclear for six studies [4, 1620]. Each of these studies included only patients whose pathologic confirmation was performed via surgical resection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from the QUADAS-2 analysis are presented in Table 2. The risk of bias in patient selection was classified as unclear for six studies [4, 1620]. Each of these studies included only patients whose pathologic confirmation was performed via surgical resection.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of risk of bias related to the index test (MRI interpretation), most studies were designated low risk. One study had a potentially high risk of bias related to the index test because the interpreting radiologists were not blinded to clinical or laboratory information [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach would be to use preoperative imaging to select those patients who have features of papillary renal cell carcinoma and only use the smaller needles when performing biopsies in these patients. Distinguishing imaging characteristics have been described on computed tomography (enhancement and attenuation values), magnetic resonance imaging (T2‐weighted hyperattenuation and of low signal on T2‐weighted images and apparent diffusion coefficient), positron emission tomography (standardized uptake value maximum), and contrast‐enhanced ultrasound (speed and extent of enhancement, washout) . It is unknown whether adding some form of ablative agent or gel to the biopsy site before removing the needle would reduce the possibility of tumor cells being drawn backward into the needle track, although preliminary animal studies have suggested it may be possible …”
Section: Introductionmentioning
confidence: 99%